2017
DOI: 10.1093/ve/vex032
|View full text |Cite
|
Sign up to set email alerts
|

Divergent HIV-1 strains (CRF92_C2U and CRF93_cpx) co-circulating in the Democratic Republic of the Congo: Phylogenetic insights on the early evolutionary history of subtype C

Abstract: Molecular epidemiological studies revealed that the epicenter of the HIV pandemic was Kinshasa, the capital city of the Democratic Republic of the Congo (DRC) in Central Africa. All known subtypes and numerous complex recombinant strains co-circulate in the DRC. Moreover, high intra-subtype diversity has been also documented. During two previous surveys on HIV-1 antiretroviral drug resistance in the DRC, we identified two divergent subtype C lineages in the protease and partial reverse transcriptase gene regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 60 publications
(63 reference statements)
3
18
0
Order By: Relevance
“…The exponential growth coupled with a strict molecular clock suggests steady transmission and diversification of viral lineages over time. The estimated growth rates were similar for the two genetic regions and were in the same order of magnitude as those of HIV group M in the prepandemic period (Faria et al., ; Villabona Arenas et al., ). The upper bound of the tMRCA for SIVgor in this particular region was around the late 1930s in line with the idea that SIVs are in general young lentiviral lineages (Wertheim & Worobey, ).…”
Section: Discussionmentioning
confidence: 60%
“…The exponential growth coupled with a strict molecular clock suggests steady transmission and diversification of viral lineages over time. The estimated growth rates were similar for the two genetic regions and were in the same order of magnitude as those of HIV group M in the prepandemic period (Faria et al., ; Villabona Arenas et al., ). The upper bound of the tMRCA for SIVgor in this particular region was around the late 1930s in line with the idea that SIVs are in general young lentiviral lineages (Wertheim & Worobey, ).…”
Section: Discussionmentioning
confidence: 60%
“…The DRC66 sequence represents a sister lineage to the subtype C clade, and quite divergent: we estimate it shared a common ancestor with subtype C some 20 to 30 years before the time of the common ancestor of conventional subtype C. Parts of gag and pol from three recently described recombinant genomes from Kinshasa and Mbuji-Mayi sampled in 2008 are the only contemporary sequences that also belong to this lineage in part of their genomes. Villabona et al and Rodgers et al describe two additional so-called "divergent C lineages" sampled between 2001-2012 that are monophyletic with conventional C with respect to the DRC66 lineage, yet form separate sister lineages to subtype C (15,17). Similarly, for most other HIV-1 subtypes more divergent lineages can be found in DRC (in particular Kinshasa) and other central African countries than in other regions where the more restricted within-subtype diversity arose in a relatively short time after founder events.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive BLAST searches and searches via neighbor-joining trees of downloaded HIV-1 sequences revealed that DRC66 is the only reported near-complete genome from this lineage. However, the subtype-C like portions of the genomes of three recently described circulating-recombinant-forms (designated CRF93_CPX) from Kinshasa and Mbuji-Mayi, DRC, sampled in 2008 (15), formed a monophyletic group with DRC66 in a maximum likelihood tree of a partial pol alignment ( Figure 1C). Partial pol sequences of other so-called "divergent C lineages" from CRF92_CU, described in Villabona et al (15) and Rodgers et al (17), were also included in this tree.…”
Section: Drc66 Is a Sister Lineage To The Subtype C Clade And Has Extmentioning
confidence: 99%
See 2 more Smart Citations